Marktkopplung und Ablaufdeterminismus: Eine Kritik am Demokratisierungsversprechen der Industrie-4.0-Diskussion - Jobst, Gaus; Christopher, Knop; David, Wandjo (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
Through the ongoing debate different positions support the hypothesis that Industry 4.0 evokes decentralization in everyday works. In this article we argue that the technological premises of Industry 4.0 lead to the contrary: centralized planning ensuing from optimized adaptation to the imperatives of the market. We exemplify this pattern, that we named ‘determinated procedure’, through exemplary cases from different industrial branches. Furthermore, we argue that (indeed) existing decentral moments neither amount to structural decentralization nor to humanizing and empowering concessions to employees, but rather primarily serve to their integration into the enterprise and mobilization of their production intelligence.